Goqu: a digital platform for transparent and accountable mosque funding - Setiawan, Erwin Dwiadji; Masyita, Annisa Diva; Muhammad Faqih, Sayyid; Raihan, Muhammad Daffa; Salsabilla, Selfira; Setiani, Novi (2025)
Mosques as centers of worship, education, and social activities for Muslims often face funding constraints, especially in remote areas. GoQu (Good Mosque Governance) is a digital-based solution that connects mosques with potential donors through an open financial reporting system. The platform displays detailed information on mosque needs (e.g., renovations, operations, programs) while allowing donors to track the use of funds in real-time. With the tagline #TransparentAccountable, GoQu ensures that every donation is recorded and monitored, enhancing public trust in Islamic philanthropy. The primary features include: (1). Database of beneficiary mosques, (2). Verified financial statements (3). Project progress updates. As a result, mosques can secure sustainable funding, while donors feel confident their contributions are being used effectively. GoQu creates a transparent donation ecosystem, supporting the strategic function of mosques as centers for the development of the people. This innovation is expected to optimise community participation in the construction of mosques through digital technology.